Aluminum Matrix Composites Reinforced with Alumina Nanoparticles - Casati, Riccardo (PoliMI SpringerBriefs, 2016)
This book describes the latest efforts to develop aluminum nanocomposites with enhanced damping and mechanical properties and good workability. The nanocomposites exhibited high strength, improved damping behavior and good ductility, making them suitable for use as wires. Since the production of metal matrix nanocomposites by conventional melting processes is considered extremely problematic (because of the poor wettability of the nanoparticles), different powder metallurgy routes were investigated, including high-energy ball milling and unconventional compaction methods. Special attention was paid to the structural characterization at the micro- and nanoscale, as uniform nanoparticle dispersion in metal matrix is of prime importance. The aluminum nanocomposites displayed an ultrafine microstructure reinforced with alumina nanoparticles produced in situ or added ex situ. The physical, mechanical and functional characteristics of the materials produced were evaluated using different mechanical tests and microstructure investigation techniques. The book presents and discusses the experimental results in detail, and offers suggestions for future research directions.